ملامح الاتجاه الأدبي الاجتماعي في تفسير الأزهر للعلامة الحاج عبد المالك كريم أمر الله - Sutrisno Hadi (Universitas Islam Negeri Mataram, 2014)
Among other interpretation patterns of the Qur’an, the social pattern is the most prominent at this time due to its emphasis on efforts to actualization of the Qur’an guidance in various aspect of life as well as harmonization of the teachings of Islam with the times. One of the most distinguished works in this type in Indonesia is that of Hamka, Tafsir Al-Azhar. This article is aimed at analyzing the work to define how consistent the author to be in line with the characteristics of the interpretation pattern in terms of its background and objectives, bibliographies it refers to, and its methodology. It is found that the author, Hamka, is very consistent to be in line with social interpretation pattern of the Qur’an.